2021
DOI: 10.3390/polysaccharides2030035
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Biodegradation Properties of Graphene Derivatives/Thermoplastic Starch Composites

Abstract: Development of biodegradable materials for packaging is an issue of the utmost importance. These materials are an alternative to petroleum-based polymers, which contribute to environment pollution after disposal. In this work, graphene oxide (GO) and glucose-reduced graphene oxide (rGO-g) were incorporated to thermoplastic starch (TPS) by melt extrusion. The TPS/GO and TPS/rGO-g composites had their physical properties and biodegradability compared. X-ray diffraction (XRD) showed that the type of graphene used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The enhanced biodegradability of the composite film can be attributed to the faster biodegradability of both keratin and GO due to enzymatic activity by different microorganisms 3,22,36 . Furthermore, it was observed that the presence of GO accelerated the rate of decomposition for the fabricated composite 19,37 . The significant increase in biodegradability of the keratin‐GO composite film has promising implications for the development of sustainable and eco‐friendly materials.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The enhanced biodegradability of the composite film can be attributed to the faster biodegradability of both keratin and GO due to enzymatic activity by different microorganisms 3,22,36 . Furthermore, it was observed that the presence of GO accelerated the rate of decomposition for the fabricated composite 19,37 . The significant increase in biodegradability of the keratin‐GO composite film has promising implications for the development of sustainable and eco‐friendly materials.…”
Section: Resultsmentioning
confidence: 96%
“…3,22,36 Furthermore, it was observed that the presence of GO accelerated the rate of decomposition for the fabricated composite. 19,37 The significant increase in biodegradability of the keratin-GO composite film has promising implications for the development of sustainable and eco-friendly materials. The resulting composite material retains the desirable properties of keratin, such as biocompatibility and biodegradability, while exhibiting improved biodegradability attributed to the presence of GO.…”
Section: Biodegradability Testmentioning
confidence: 99%
“…Three random strips of dimension 2 × 2 cm 2 were cut from pure PCF and S 3 and the results are given as mean of three samples, whereas PCF film was used as a control. The degradation rate was nearness for the increased biodegradability of fabricated composite film S 3 was a favorable hydrophilic condition by incorporating GO in PCF which is suitable for increasing enzymatic activity by different microorganisms [42].…”
Section: Xrd Analysismentioning
confidence: 91%
“…TG is another valuable method for assessing biodegradation on polymers. Changes in the TG curve can indicate polymer structure modifications and additive loss [57,59,62,63,77,90]. High-resolution TGA allowed Quintana et al (2013) [77] to quantify the amount of plasticizer lost when plasticized cellulose acetate films were subjected to accelerated weathering.…”
Section: Methods Based On Thermal Propertiesmentioning
confidence: 99%